A brief diagnostic screen for cluster headache: Creation and initial validation of the Erwin Test for Cluster Headache. (November 2021) - Parakramaweera, Randika; Evans, Randolph W; Schor, Larry I; Pearson, Stuart M; Martinez, Rebecca; Cammarata, Jacob S; Amin, Amisha J; Yoo, Seung-Hee; Zhang, Wei; Yan, Yuanqing; Burish, Mark J
Abstract: Objective: To use 1) newly generated data, 2) existing evidence, and 3) expert opinion to create and validate a new cluster headache screening tool. Methods: In phase 1 of the study, we performed a prospective study of an English translation of an Italian screen on 95 participants (45 with cluster headache, 17 with other trigeminal autonomic cephalalgias, 30 with migraine, and 3 with trigeminal neuralgia). In phase 2, we performed a systematic review in PubMed of all studies until September 2019 with diagnostic screening tools for cluster headache. In phase 3, a 6-person panel of cluster headache patients, research coordinators, and headache specialists analyzed the data from the first two phases to generate a new diagnostic screening tool. Finally, in phase 4 this new screen was validated on participants at a single headache center (all diagnoses) and through research recruitment (trigeminal autonomic cephalalgias only, as recruitment was essential but was otherwise low). Results: In total, this study included 319 unique participants including 109 cluster headache participants (95 total participants/45 cluster headache participants in phase 1, and 224 total participants/64 cluster headache participants in phase 4). It also found 123 articles on potential screening tools in our systematic review. In phase 1, analysis of the English translation of an Italian screen generated 7 questions with high sensitivity and specificity against migraine, trigeminal neuralgia, and other trigeminal autonomic cephalalgias, but had grammatical and other limitations as a general screening tool. In phase 2, the systematic review revealed nine studies that met inclusion criteria as diagnostic screening tools for cluster headache, including four where sensitivity and specificity were available for individual questions or small groups of questions. In phase 3, this data was reviewed by the expert panel to generate a brief (6-item), binary (yes/no), written screening test. In phase 4, a total of 224 participants completed the new 6-item screening test (81 migraine, 64 cluster headache, 21 other trigeminal autonomic cephalalgias, 35 secondary headaches, 7 neuralgias, 5 probable migraine, and 11 other headache disorders). Answers to the 6 items were combined in a decision tree algorithm and three items had a sensitivity of 84% (confidence interval or 95% confidence interval 73–92%), specificity of 89% (95% confidence interval 84–94%), positive predictive value of 76% (95% confidence interval 64-85%), and negative predictive value of 93% (95% confidence interval 88–97%) for the diagnosis of cluster headache. These three items focused on headache intensity, duration, and autonomic features. Conclusion: The 3-item Erwin Test for Cluster Headache is a promising diagnostic screening tool for cluster headache.